BOTANICAL ELIXIRS: A RARE CASE OF SUICIDAL POISONING WITH A FLOWER STIMULANT (Journal of Forensic Medicine & Toxicology, 2025)
Nitrobenzene-based flowering stimulants are rare causes of fatal poisoning. This case highlights acute methemoglobinemia due to ingestion of a stimulant, describing clinical, autopsy, and toxicological findings.
Keywords: Flower stimulant poisoning; Nitrobenzene; Acute methemoglobinemia; Methylene blue infusions; Thin layer chromatography